Nanoparticle shape effects on squeezed MHD flow of water based Cu, Al2O3 and SWCNTs over a porous sensor surface - Kandasamy, Ramasamy; Adnan, Nur Atikah; Mohammad, Radiah (Elsevier, 2017)
Impact of nanoparticle shape on the squeezed MHD flow of water based metallic nanoparticles over a porous sensor surface in the presence of heat source has been investigated. In distinctly most paramount studies, three distinctive forms of nanoparticle shapes are employed into account, i.e. sphere ðm ¼ 3:0Þ, cylinder ðm ¼ 6:3698Þ and laminar ðm ¼ 16:1576Þ. The controlling partial differential equations (PDEs) are regenerated into ordinary differential equations (ODEs) by manipulating consistent conformity conversion and it is determined numerically by handling Runge Kutta Fehlberg method with shooting technique. It is noticed that the solid volume fraction and nanoparticle shape have powerful outputs in squeezing flow phenomena, the sphere shape nanoparticle in Cu – water and cylindrical shape in SWCNTs-water in the presence of magnetic field along with thermal radiation energy has better improvement on heat transfer as compared with the other nanoparticle shapes in different flow regimes.